Assessing low free gas saturation via acoustic velocity in porous media - Shi, Rengang; Wang, Jianwu; Wei, Zhoutuo; Ge, Xinmin; Xing, Lei; Zhao, Junfeng (Frontiers in Earth Science, 2025)
This study proposes a novel quantitative evaluation method for acoustic logging velocities in sedimentary porous media with free gas saturation below 2%. This issue is of critical importance for gas migration analysis, geological hazard prediction, and environmental safety monitoring; however, conventional rock physics models suffer from significantly diminished accuracy in scenarios with ultra-low gas saturation and are unable to capture the pronounced nonlinear changes in acoustic velocity. To address these challenges, a dynamic coupling factor J is introduced within a revised Biot theoretical framework, and, in conjunction with core experimental data, the associated dynamic and elastic parameters are systematically optimized with respect to gas saturation. The new model accurately reflects the rapid decline of P-wave velocity with increasing gas content in the 0–2% saturation range, reducing velocity prediction error from 55.7% (typical of traditional approaches) to just 5.27%. Application to well-logging data from the LS-361 site in the South China Sea demonstrates that the model is capable of effectively resolving gas-bearing layers with extremely low saturations (0–0.12%), thereby verifying its practical utility. This method significantly enhances the quantitative interpretability of subtle free gas indicators in subseafloor sediments and advances the theoretical understanding of multiphase poroelastic mechanisms, contributing to improved accuracy in gas reservoir identification and environmental risk assessment.